2020
DOI: 10.1101/2020.06.21.163428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aberrant regulation of a poison exon caused by a non-coding variant inScn1a-associated epileptic encephalopathy

Abstract: Dravet syndrome (DS) is a developmental and epileptic encephalopathy that results from mutations in the Na v 1.1 sodium channel encoded by SCN1A. Most known DS-causing mutations are in coding regions of SCN1A, but we recently identified several disease-associated SCN1A mutations in intron 20 that are within or near to a cryptic and evolutionarily conserved "poison" exon, 20N, whose inclusion leads to transcript degradation. However, it is not clear how these intron 20 variants alter SCN1A transcript processing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Voskobiynyk and colleagues [ 10 ] then proceed to assess poison exon inclusion and found that up to 70% of SCN1A transcripts included exon 20N during embryonal development, which decreased over time to 10% postnatally. This suggests that poison exon inclusion is not just an epiphenomenon, but an active regulatory process to suppress SCN1A expression during early development.…”
Section: Persistent Poison Exon Inclusion Results In Aberrant Fetal Ementioning
confidence: 99%
See 1 more Smart Citation
“…Voskobiynyk and colleagues [ 10 ] then proceed to assess poison exon inclusion and found that up to 70% of SCN1A transcripts included exon 20N during embryonal development, which decreased over time to 10% postnatally. This suggests that poison exon inclusion is not just an epiphenomenon, but an active regulatory process to suppress SCN1A expression during early development.…”
Section: Persistent Poison Exon Inclusion Results In Aberrant Fetal Ementioning
confidence: 99%
“…In the study by Voskobiynyk and colleagues [ 10 ], the authors provide a deep dive into regulation of SCN1A through poison exons. The SCN1A gene contains the naturally occurring poison exon 20N, and inclusion of this exon results in nonproductive splicing and nonsense-mediated RNA decay, effectively reducing the amount of Nav1.1-containing sodium channels made available to neurons.…”
Section: A Mouse Model Due To An Scn1a Poison Exonmentioning
confidence: 99%
“…Probands A, B, and C have variants within intron 20 of SCN1A and each has seizure phenotypes that are consistent with SCN1A-associated epilepsy (see Case Reports in Supplemental Data 4). This intron harbors the 20N poison exon 9 variants in or near to 20N have been previously associated with epilepsy in both humans and mice 8,11 . The phenotype of Proband B also included developmental delay and spastic dystonic cerebral palsy with left triplegia.…”
Section: Poison Exon Variantsmentioning
confidence: 99%
“…The inclusion of PTCs cause translation to stall, thereby triggering nonsense-mediated decay (NMD) of the transcript and reducing protein levels in the cell. Some PEs are spliced into transcripts at relatively high levels during mammalian brain development in early stages and are hypothesized to regulate protein levels of the genes in which they reside 7,8,9,10 . Crucially, since PE usage leads to NMD, and therefore reduction of protein, genetic variation that alters PE inclusion can lead to a loss-of-function effect.…”
Section: Introductionmentioning
confidence: 99%
“…If technology for allelespecific targeting were to be improved [16], however, then NHEJ might be harnessed to destroy a gene variant that acts in a dominant or dominant negative manner, in a context where haploinsufficiency of the gene product results in a less severe phenotype [17]. A possibility for genetic epilepsy, and an as of yet untested strategy, could be to use CRISPR to destroy the splice-site of the recently discovered poison exon (20 N) in SCN1A, in order to permanently upregulate SCN1A expression in Dravet syndrome [18,19]. Proof-of-principle of such an approach has been demonstrated using Targeted Augmentation of Nuclear Gene Output (TANGO) technology, which uses an antisense oligonucleotide targeted to the poison exon of Scn1a to reduce a non-productive alternative splicing event [20].…”
Section: Cas9 Endonuclease-mediated Gene Editingmentioning
confidence: 99%